Perbandingan Struktur Tuned Mass Damper dan Struktur Fixed Base dengan Metode Performance Base Design - Maulidani, Andra Akmal; Sulton, Mohammad; Umniati, B. Sri; Maulida, Alfia Salma Mei (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
Indonesia's location in an earthquake zone with moderate to high intensity increases the urgency of planning high-rise earthquake-resistant buildings. Losses that occur due to the absence of procedures to predict earthquakes properly and accurately, make it important to innovate structural systems and evaluate their performance against earthquakes. This study aims to determine the impact of adding Tuned Mass Damper to buildings viewed from the level of structural performance compared to Fixed Base structures. Performance Base Design based on FEMA 440, is a design that categorizes the target damage to building structures into 4 levels of damage reviewed from the percentage of story deviation to the total height of the structure. Tuned Mass Damper is an innovation in structural systems consisting of mass, springs, and dampers installed to absorb their dynamic response. Pendulum Tuned Mass Damper is a Tuned Mass Damper system using a pendulum swinging relative to the floor motion. The addition of Tuned Mass Damper to Fixed Base type buildings causes a decrease in deviation of up to 19% from the original deviation depending on the mass ratio. This addition also reduces the value of the structural period by up to 9% with the period still below the maximum period standard. In addition, the addition of Tuned Mass Damper also reduces the target value of structural displacement based on FEMA 440 by 52% with the immediate occupancy building performance level.